In vivo nonlinear imaging of corneal structures with special focus on BALB/c and streptozotocin-diabetic Thy1-YFP mice. (May 2016) - Ehmke, Tobias; Leckelt, Janine; Reichard, Maria; Weiss, Heike; Hovakimyan, Marina; Heisterkamp, Alexander; Stachs, Oliver; Baltrusch, Simone
Abstract: Two-photon microscopy (TPM) allows high contrast imaging at a subcellular resolution scale. In this work, the microscopy technique was applied to visualize corneal structures in two mouse models (BALB/c and B6.Cg-Tg(Thy1-YFP)16Jrs/J) in vivo . In particular, the transgenic Thy1-YFP mice expressing the yellow fluorescent protein (YFP) in all motor and sensory neurons had been used for investigating the nerve fiber density in healthy and streptozotocin-diabetic mice. This model is clinically relevant since patients suffering from diabetes mellitus have a high risk to develop small fiber neuropathy. Nonlinear laser scanning microscopy displayed a reduction of nerve fiber density in streptozotocin-diabetic versus healthy mice and confirmed data obtained by confocal laser scanning microscopy (CLSM). In recent years, corneal CLSM was proved to be an appropriate non-invasive tool for an early diagnosis of diabetic neuropathy. Nevertheless, validation of the CLSM method for the clinical routine is currently a matter of investigation and requires confirmation by further studies and complementary techniques. Thus, the present study provides further evidence of corneal confocal microscopy as a promising technique for non-invasive detection of diabetic neuropathy. Information derived from these experiments may become clinically relevant and help to develop new drugs for treatment of diabetic neuropathy. Highlights: We show nonlinear and confocal microscopy for corneal in vivo imaging in mouse models. Advanced imaging modalities reduce motion artifacts resulting in high quality images. Both techniques can identify diseases in normal and transgenic animal models in vivo. Diabetic mice show a reduced corneal nerve fiber density compared to controls. Results of nonlinear microscopy confirm results of confocal microscopy.